2018
DOI: 10.1007/s11096-018-0692-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a risk model for predicting QTc interval prolongation in patients using QTc-prolonging drugs

Abstract: Background Numerous drugs prolong the QTc interval on the ECG and potentially increase the risk of cardiac arrhythmia. This risk is clinically relevant in patients with additional risk factors. Objective The objective was to develop and validate a risk model to predict QTc interval prolongation of eligible ECGs. Setting Spaarne Gasthuis (Haarlem/Hoofddorp, The Netherlands). Method A dataset was created from ECGs recorded in patients using one or more QTc prolonging drugs, in the period January 2013 and October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 21 publications
0
30
0
1
Order By: Relevance
“…People with COVID-19 may have several cardiovascular risk factors, including (a) old age; (b) pre-existing comorbid cardiovascular diseases; (c) use of medical treatments with QTc-prolonging properties, often in combination (e.g., antivirals, chloroquine/hydroxychloroquine and antibiotics); (d) a possible direct cardiotoxic effects of the coronavirus; and (e) electrolyte alterations related to abnormal respiratory gas exchange [ 3 , 20 , 87 , 92 , 97 ]. The most important risk factors of severe arrhythmias, such as torsade de pointes, include the magnitude of QTc prolongation, pre-existing heart disease, female sex, bradycardia, hypokalemia, and other electrolyte abnormalities [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…People with COVID-19 may have several cardiovascular risk factors, including (a) old age; (b) pre-existing comorbid cardiovascular diseases; (c) use of medical treatments with QTc-prolonging properties, often in combination (e.g., antivirals, chloroquine/hydroxychloroquine and antibiotics); (d) a possible direct cardiotoxic effects of the coronavirus; and (e) electrolyte alterations related to abnormal respiratory gas exchange [ 3 , 20 , 87 , 92 , 97 ]. The most important risk factors of severe arrhythmias, such as torsade de pointes, include the magnitude of QTc prolongation, pre-existing heart disease, female sex, bradycardia, hypokalemia, and other electrolyte abnormalities [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bindraban risk model for predicting QTc interval prolongation in patients using QTc-prolonging drugs. 41 A risk model to predict QTc interval prolongation of eligible ECGs. The model was developed by examining ECGs recorded in patients using one or more QTcprolonging drugs.…”
Section: Tool Descriptionmentioning
confidence: 99%
“…The fourth theme, limited availability of protocols, is possibly related to the limited routine use of risk scoring tools in practice. Although there are several QTcI prolongation risk scoring tools published in the literature, 14,[36][37][38] cardiologists in our study were either not aware or argued they had limited time to utilize them in practice. Some studies have shown that risk stratification and implementation of a standardized QTcI monitoring protocol can provide relevant clinical guidance in treatment decisions and result in positive patient outcomes.…”
Section: Discussionmentioning
confidence: 94%